Volatility in the Foreign Exchange and Stock Markets: Is It Excessive? - Hodrick, Robert J. (American Economic Review, 1990)
This paper examines recent theoretical and empirical analyses that may help us understand and eventually model the observed movements of foreign exchange rates and stock prices. Whether these prices are rational, efficient, and hence not excessively volatile is, of course, a joint hypothesis. The question in the title can never be answered in the abstract. We must always compare actual volatility to the volatility implied by a benchmark model.